The utilization of rice husk silica as a catalyst: review and recent progress - Adam, Farook; Appaturi, Jimmy Nelson; Mohamed Iqbal, Mohammad Anwar (Elsevier, 2012)
In this review article, we report the recent development and utilization of silica from rice husk (RH)for the immobilization of transition metals and organic moieties. Silicon precursor was obtained in the form of sodium silicate and as rice husk ash (RHA). Sodium silicate was obtained by direct silica extraction from rice husk via a solvent extraction method while rice husk ash was obtained by pyrolyzing the RH in the range of 500–800 ◦C for 5–6 h. Transition metals were immobilized into the silica matrix via the sol–gel technique while the organic moieties were incorporated using a grafting method. 3- (Chloropropyl)triethoxy-silane (CPTES) was used as a bridge to link the organic moieties to the silica matrix. All the catalysts exhibited good physical and catalytic potential in various reactions.